SOIL BIOLOGY CONTRIBUTION ON AGRICULTURAL LAND SUITABILITY EVALUATION OF WET TROPICAL MEGABIODIVERSITY REGIONS - GITOSUWONDO, SUBOWO; SANTOSA, EDI; ANAS, ISWANDI (Indonesian Center for Agriculture Land Resource Development, 2010)
Indonesia is in the region